Permanent Education in Family Health Units: comprehension of the multiprofessional team - Silvério de Moraes, Rafael; Ribeiro Higa, Elza de Fátima; Alves de Moraes, Magali Aparecida (O Mundo da Saúde, 2022)
In Brazil, Permanent Education in Health was established by the National Policy of Permanent Education for Social Control in the Unified Health System (UHS); this strategy advocates the development and training of health professionals. This study aimed to characterize the activities developed and the understanding of Permanent Health Education in the Family Health Units by the multiprofessional team. This was a qualitative study whose data were collected with 50 professionals from the teams of 12 Family Health Units (FHU) in the city of Assis in the interior of the State of São Paulo through semi-structured interviews and were submitted to Content Analysis, by a Thematic modality. The analysis of the nuclei of meanings of the data obtained in the interview showed two thematic categories: a) Activities of Permanent Education in Health - home visits, team meeting, guidelines on procedural techniques in different places of care, and the absence of activities; and b) Understandings of Permanent Education in Health - regular meetings of the team to work on teaching in healthcare, learning from the difficulties to build new knowledge, joint discussion to solve people’s health problems, and the continuous monitoring of current diseases. There is a clear need for new studies to complement and contribute to the expansion of knowledge for the incorporation of PHE in the practice of care developed by the multidisciplinary teams of the FHU.